Pengaruh Beberapa Jenis Karbohidrat dalam Pakan Terhadap Pertumbuhan Benih Gurami (Osphronemus goramy Lac.) yang Berumur Diatas 80 Hari [The Effect Of Some Carbohydrates In The Diet On The Growth Of Giant Gouramy Fry, Osphronemus goramy Lac. Above 80 Days Old] - Yudi Cahyoko (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract When small giant gouramy fry, 40 to 80 days old can consume carbohydrate diet, starch but his growth slow. Conversely, when he consumes simple carbohydrate, his growth is faster. Considering that feedstuffs derive from plants containning much complex carbohydrates like starch that is easier obtained and relatively cheaper price, so, it is important to study utilization of the starch as feedstuff on the diet of the giant gouramy fry. This research was carried out to find out type of carbohydrate that is suitable for giant gouramy fry above 80 days old. For achieving this purpose, it was important to test utilization of the diet containing starch compared with diet containing glucose, sucrose and dextrin on the growth of the giant gouramy fry. The giant gouramy fry was fed diet containing 27.68 % of glucose, sucrose, dextrin and starch each. The Feedstuffs in the diet were composed isocalorie and isoprotein. The giant gouramy fry that tested was 130 days old and average weight 6.90 grams. The fishes were cultured with stocking rate 5 fishes per 60 litre of water and cultured for 60 days. The diet that contains starch resulted the same on daily average growth rate to compare glucose, sucrose and dextrin ( P > 0.05 ). Sucrose diet resulted protein retention, lipid retention and energy retention higher than starch diet ( P < 0.01 ). Starch diet resulted the lowest retention of protein, lipid and energi ( P < 0.01 ). It was concluded that the sucrose was the best carbohydrate source for the giant gouramy fry, 130 to 190 days old. The starch was not suitable yet as source of carbohydrate to compose diet of the giant gouramy fry, 130 to 190 days old or average weigh 6.90 to 16.50 gram.